Analysis of the Use of Gen Z Terminology on the Purchase of Fashion Trends of Jims Honey Products on the Tiktok Platform - Napitu, Christin; Pinem, Dhea; Hutagalung, Sondang Lamsarina; Marpaung, Agung; Irawan, Desi; Zahra, Atika; Dalimunthe, Syairal Fahmy (CV. Rayyan Dwi Bharata, 2024)
The study aims to find out the level of use of the term gen z in the TikTok platform towards the purchase of Jims Honey fashion products. The research was also made to find out what words Jims Honey uses in their fashion content on TikTok. The information in this study was obtained by listening to words or terms written on TikTok social media videos. The method used in the study is the Qualitative Descriptive Method. Information processing is carried out using documentation on the TikTok platform. This study was also made to determine the influence of the use of the term gen z or slank language on costumer purchase decisions. The results of this study show that the level of use of the term gen z in the TikTok platform increases the attractiveness and interest of consumers or costumers in purchasing fashion trends on Jims Honey products.